Study on Meshing Efficiency of Non-circular Gear based on Elastohydrodynamic Lubrication - Wanshan Liu; Hao Peng; Zhiqin Cai; Xiaofan Ma (Jixie chuandong)
Based on the analysis of the meshing characteristics of non-circular gear and the law of equal engagement angle of tooth profile， considering the influence of relative speed， friction coefficient， oil film thickness， and other key factors on the loss of meshing power， a novel mathematical model for the meshing efficiency of non-circular gear transmission under the elastohydrodynamic lubrication condition is established. By defining a meshing cycle as the period from the tooth top of pitch curve trough to the tooth root of pitch curve crest of non-circular gear， the meshing efficiency of noncircular gear drive is obtained by calculating the power loss of sliding friction and rolling friction under the change of meshing angle.